PELATIHAN ROBOTIKA BERBASIS ANDROID UNTUK MENUMBUHKAN INOVASI DAN KREATIVITAS DI SMP 11 BANDUNG - mujiarto, mujiarto; Sambas, A; Gundara, Gugun; Ula, Shofiatul (Universitas Muhammadiyah Tapanuli Selatan, 2019)
This training aims to create an arduino robot that is controlled using android. The initial study of this research was to design a Proteus simulation to test the performance of robots. Next, design the robot by combining the motor driver, wheel engine and Arduino. Finally, integrate the robot with Android to control the robot's navigation system. This Android-based Arduino robot training will be introduced to students in the robotics workshop at SMP 11 Bandung as a medium for teaching physics or electronics. With this training, it is expected that students will be able to increase innovation and more creativity towards the subjects taught.